1983
DOI: 10.1080/03610738308258447
|View full text |Cite
|
Sign up to set email alerts
|

Spatial knowledge of young and elderly adults: Scene recognition from familiar and novel perspectives

Abstract: Thirty young adults (mean age = 25.3) and 30 elderly adults (mean age = 65.3) were tested on a memory task in which they were asked to recognize environmental scenes from familiar and novel perspectives. Participants initially viewed slides of 10 business and 10 residential street intersections. Pairs of intersections were then presented and subjects were asked to select the intersection viewed previously. During the recognition phase subjects saw the intersections from the original perspective (0 degrees), ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The hippocampus appears to be an early target of age-related structural and physiological changes (Hasan and Glees 1973) and damage to the hippocampus results in similar cognitive impairments as experienced by elderly people (Barnes 1979, 1988; Gallagher and Nicolle 1993; Geinisman et al 1986). Considerable evidence supports that aged humans have trouble navigating or finding their way in a large environment and remembering spatial relationships among landmarks (Bruce and Herman 1983; Caplan and Lipman 1995; Cherry and Park 1989; Evans et al 1984; Flicker et al 1984; Kirasic 1991; Kirasic et al 1992; Kirasic and Bernicki 1990; Lipman and Caplan 1992; Moffat et al 2001; Naveh-Benjamin 1987; Ohta et al 1981; Park et al 1990; Perlmutter et al 1981; Sharps and Gollin 1987; Thomas 1985; Uttl and Graf 1993; Weber et al 1978; Wilkniss et al 1997; Zelinski and Light 1988). In some studies, humans show a 30–80% drop in performance of spatial memory tasks with advancing age (Cherry and Park 1993; Evans et al 1984; Kirasic and Bernicki 1990; Moffat et al 2001; Moore et al 1984; Sharps and Gollin 1987).…”
Section: What Is Learning and Memory?mentioning
confidence: 99%
“…The hippocampus appears to be an early target of age-related structural and physiological changes (Hasan and Glees 1973) and damage to the hippocampus results in similar cognitive impairments as experienced by elderly people (Barnes 1979, 1988; Gallagher and Nicolle 1993; Geinisman et al 1986). Considerable evidence supports that aged humans have trouble navigating or finding their way in a large environment and remembering spatial relationships among landmarks (Bruce and Herman 1983; Caplan and Lipman 1995; Cherry and Park 1989; Evans et al 1984; Flicker et al 1984; Kirasic 1991; Kirasic et al 1992; Kirasic and Bernicki 1990; Lipman and Caplan 1992; Moffat et al 2001; Naveh-Benjamin 1987; Ohta et al 1981; Park et al 1990; Perlmutter et al 1981; Sharps and Gollin 1987; Thomas 1985; Uttl and Graf 1993; Weber et al 1978; Wilkniss et al 1997; Zelinski and Light 1988). In some studies, humans show a 30–80% drop in performance of spatial memory tasks with advancing age (Cherry and Park 1993; Evans et al 1984; Kirasic and Bernicki 1990; Moffat et al 2001; Moore et al 1984; Sharps and Gollin 1987).…”
Section: What Is Learning and Memory?mentioning
confidence: 99%
“…7,8 Several studies have found that RL is impaired in AD and mild cognitive impairment (MCI) by way of questionnaires, 3,9 real-world scenarios, [10][11][12][13][14][15] or virtual reality testing. Furthermore, a decline of RL in normal elderly subjects, [24][25][26][27][28][29][30][31] and sex differences in tasks of topographical orientation have been reported. These findings have augmented our concept of navigation in dementia.…”
mentioning
confidence: 94%
“…Spatial memory decline is a phylogenetically conserved trait and has been observed in invertebrates (Münch et al, 2010), rodents (Barnes et al, 1980; Wyss et al, 2000), non-human primates (Lacreuse et al, 2005), and humans (Bruce and Herman, 1983; Moffat et al, 2001). Spatial memory, or the memory niche responsible for remembering one's environments and surroundings, is primarily managed by the hippocampus of the mammalian brain (Scoville and Milner, 1958), and indeed the hippocampal volume has been shown to be decreased with age (Convit et al, 1995; Mu et al, 1999; Driscoll et al, 2003).…”
Section: Introductionmentioning
confidence: 99%